2021
DOI: 10.1021/acs.analchem.1c01254
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Peptide-Functionalized Biomimetic Nanointerfaces for Synergetic Capture of Circulating Tumor Cells in an EpCAM-Independent Manner

Abstract: Broad-spectrum detection and long-term monitoring of circulating tumor cells (CTCs) remain challenging due to the extreme rarity, heterogeneity, and dynamic nature of CTCs. Herein, a dual-affinity nanostructured platform was developed for capturing different subpopulations of CTCs and monitoring CTCs during treatment. Stepwise assembly of fibrous scaffolds, a ligand-exchangeable spacer, and a lysosomal protein transmembrane 4 β (LAPTM4B)-targeting peptide creates biomimetic, stimuli-responsive, and multivalent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…Over 98% of HepG2 cells can be readily captured even at a cell count of 10 4 , while <0.43% of white blood cells (WBC, 10 5 to 10 7 ) were retained by Apt-Avi-BCN (Figure B). In the present case, HepG2 cells exhibit a low expression level of EpCAM . Their high capture efficiency by Apt-Avi-BCN clearly indicated that HepG2 binds to TLS11a in an EpCAM-independent manner.…”
Section: Resultsmentioning
confidence: 47%
See 1 more Smart Citation
“…Over 98% of HepG2 cells can be readily captured even at a cell count of 10 4 , while <0.43% of white blood cells (WBC, 10 5 to 10 7 ) were retained by Apt-Avi-BCN (Figure B). In the present case, HepG2 cells exhibit a low expression level of EpCAM . Their high capture efficiency by Apt-Avi-BCN clearly indicated that HepG2 binds to TLS11a in an EpCAM-independent manner.…”
Section: Resultsmentioning
confidence: 47%
“…The clinical utility of the Apt-Avi-BCN interface was further evaluated by analyzing blood samples from 20 HCC patients and 17 healthy volunteers without pretreatment. In each assay, 0.5 mL of whole blood was conducted with the capture/release process followed by a standard three-color immunocytochemistry staining protocol . The cells with CD45-negative and DAPI- and CK-positive staining (DAPI + /CK + /CD45 – ) were recognized as CTCs, whereas those stained positive for CD45 and DAPI but negative for CK (DAPI + /CK – /CD45 + ) were identified as WBCs (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…Immunoaffinity-based platforms usually use molecular probes such as antibodies ( Yin et al, 2018 ; Chen et al, 2019 ; Chu et al, 2019 ; Cui et al, 2019 ), peptides ( Peng et al, 2017 ; Tian et al, 2019 ; Zhong et al, 2021 ), and aptamers ( Chen et al, 2019 ; Dharmasiri et al, 2009 ; Qin et al, 2020 ) for CTC enrichment and isolation. A simple summary of the nanomaterial-based platforms for the immunocapture of CTCs is shown in Figure 1 .…”
Section: Design Principles Of Immunoaffinity Nanomaterialsmentioning
confidence: 99%
“…MNPs, magnetic nanoparticles: reproduced with permission from Tian et al (2019) , Copyright 2019, American Chemical Society. DOPA, 3,4-dihydroxy-L-phenylalanine, a key functional amino acid in mussel adhesive proteins: reproduced with permission from Zhong et al (2021) , Copyright 2021, American Chemical Society. LAPTM4B, lysosomal protein transmembrane 4 β with extraordinarily high expression level in a majority of solid tumors.…”
Section: Design Principles Of Immunoaffinity Nanomaterialsmentioning
confidence: 99%
“…Peptides with various functionalities, such as specific targeting, stimuli-responsive, cell penetration and therapeutic potential, can be delicately incorporated in a nano-system to achieve disease diagnosis and therapy [ [2] , [3] , [4] , [5] , [6] ]. Compared to non-peptide compounds, peptide-based nanomaterials possess huge potential applications due to its programmability, biological activity and good biocompatibility [ 7 , 8 ]. In the past decades, the rapid development of peptide dendrimers in the field of bio-applications, especially in cancer diagnostics and therapy, has revolutionized conventional health care and medical technology [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%